PEREMPUAN DAN ALAM YANG MELAHIRKAN KEHIDUPAN DALAM TIGA CERPEN KARYA EKA KURNIAWAN - Latif, Vivi Adriana; Abidin, Aslan; Ridwan, Ridwan (Magistra Andalusia: Jurnal Ilmu Sastra, 2023)
This research examines three short stories in the collection of short stories Broken Hearted Woman Who Finds Love Through Dreams Again by Eka Kurniawan. The research method used in this research is a qualitative method with a case study approach. Data from Kurniawan's three works are then analyzed using close reading techniques to identify themes related to women and nature. Through the perspective of ecofeminism, it seeks to reveal patriarchal dominance in the exploitation of nature and the oppression of women. Through ecofeminism, one can see how nature and women are often treated unfairly by men. This oppression resulted in resistance from women to defend themselves and protect nature.